UMKM Naik Kelas dengan Si Apik - Vivi Indah Bintari; Alfin N F Mufreni; Indi Ramadhani; Ridwan Nurul Ramadhan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are often in the spotlight in discussions about economic development. Many MSME actors currently record financial transactions until financial reports are done manually, and consider financial reports to be difficult and complicated. There are also those who think that knowledge can only be learned by highly educated people and students. . This is due to the low literacy of business actors on how to make financial reports using applications. To deal with the problems and obstacles faced by SMEs, the implementing team carried out socialization activities, preparation training and coaching on the spot. This Community Service activity aims to provide knowledge to MSME actors in making financial reports in accordance with applicable standards by utilizing digital applications made by Bank Indonesia (BI), namely the Financial Information Recording Application Information System (SI APIK), so that the preparation of business finances can be made easily and according to the rules. The method of implementing this activity is carried out in 3 stages, namely material presentation or socialization, training in preparing financial reports using the SI APIK digital application, and Coaching On The Spot. The results of this community service activity were responded positively by increasing the understanding and interest of SMEs in the Agro Commodity Processed Industry in Purbalingga regarding the preparation of good and correct financial reports. With application-based bookkeeping, it provides alternative solutions that can be applied at any time, cheaply, and efficiently. Especially in the digital era, the use of applications is very relevant for MSME business development.